IDENTIFIKASI KERUSAKAN DAUN PADA TANAMAN BALANGERAN (Shorea balangeran) DI KAWASAN HUTAN DENGAN TUJUAN KHUSUS (KHDTK) TUMBANG NUSA - Anggri Feriditya Putri; Normela Rachmawati; Dina Naemah (Universitas Lambung Mangkurat, 2021)
Damage to the plant leaves can affect the health of the plant. The research aims to identify the damage that occurs in the leaves of the Sorea balangeran plant and calculate the percentage (%) of leaf damage. The location of the study was conducted at the Tumbang Nusa KHDTK BP2LHK Banjarbaru, Central Kalimantan, determined by purposive sampling or deliberate data collection with a specified starting point, observing 639 plants on the leaf section in 2015, identifying plants based on the leaf part written in the form of a tallysheet, calculate the percentage of damages to Sorea balangeran. The types of damages that occur in the leaves include holes, rolling, yellowing, perforating and rolling, rolling and inhaling. The dominant damage to the leaf is hollow leaves by 348 and the lowest is yellow roll by 2 with a percentage of 82.26% for leaves with holes and 0.48 for leaf rolling and yellowing. The percentage of damage to the leaves of the balageran plant showed a percentage of 65.72% that on the leaves of the Balangeran plant studied showed that the leaves were not good. The conclusion from the study of the greatest leaf damage occurred due to perforated leaves and the percentage of damage to the leaves as a whole by 65.72%.Keywords: Balangeran, Damage, Leaf, Identification, Forest